Influence of MyD88 and αβ T cells on mesenteric lymph node innate lymphoid cell populations during Toxoplasma gondii infection - Jessica Belmares-Ortega; Fatouma Zara Issoufou Kapran; Eric Y. Denkers (PLoS ONE, 2025)
First encounter of Toxoplasma with the host immune system occurs within tissues of the intestine, including the intestinal mucosa and draining lymph nodes. In this study, we focused on the mesenteric lymph node compartment, the central hub of adaptive immune induction following orally acquired infection. We examined innate lymphoid cells (ILC) in mesenteric lymph nodes during Toxoplasma infection, determining the influence of MyD88 and the T lymphocyte compartment on ILC subset distribution, IFN-γ production, MHC class II expression and proliferation. Collectively, we observed an ILC1-dominated response that was impacted by both MyD88 and T lymphocytes. We also found a population of putative ILC that were negative for signature transcription factors associated with ILC1, 2 and 3 subsets. This study increases our understanding of ILC-mediated immunity during Toxoplasma infection and points to the complex interactions with which these cells engage T cell and MyD88-dependent immunity.